The price premium for organic wines: Estimating a hedonic farm-gate price equation - Alessandro Corsi; Steinar Strøm (University of Oslo, Department of Economics, 2013)
Organic wines are increasingly produced and appreciated. Since organic production is more costly, a crucial question is whether they benefit from a price premium. We estimate hedonic price functions for Piedmont organic and conventional wines. We use data on the production side in addition to variables of interest for consumers. Our results show that, along with characteristics of interest to consumers, some farm and producer characteristics not directly relevant for consumers do significantly affect wine prices. We find that organic wine tends to obtain higher prices than conventional wine. The price premium is not simply an addition to other price components, but organic quality modifies the impact of the other variables on price.
Keywords: C21; D49; L11; Q12; 330